A Rice Starch Added Follow-On Formula for Infants with Sleeping Difficulty - Pipop Jirapinyo (2018)
A total of 15 infants aged between 4-12 months with sleeping difficulty were enrolled in the study. All participants were given a test follow-on formula (cow's milk based), with added rice starch. The test formula was advised to be given at night-time for a 7-day period. Sleeping patterns were recorded 2 days prior to the study and during the 7-day study period. It was shown than 11 out of 15 cases (73.3%) had satisfactory results. Two cases (13.3%) were withdrawn from the study by their parents due to vomiting after taking the formula. We found that both cases developed concomitant respiratory tract infection one day after starting the study, and 2 cases (13.3%) were lost to follow-up. In conclusion, the majority of cases showed satisfactory results in terms of night sleeping pattern after switching to the rice starch added follow - on formula.